Peningkatan Kemampuan Membaca Pemahaman Menggunakan Metode SQ3R pada Siswa SMK Kahuripan 1 Jakarta - Anjelita Sembiring; Irna Sjafei (Medan Resource Center, 2023)
There are two aims of this research, namely: 1) describing the procedures for development learning using the SQ3R method which can improve abilities students' reading comprehension, 2) there is an increase in reading ability students' understanding using the SQ3R method. This type of research is qualitative descriptive. The data source in this research is the informant, namely the teacher Indonesian language class XII SMK Kahuripan 1 Jakarta, namely Mrs. Laili Lufti Yuli, S. Pd and class XII students. The data is in the form of an increase in reading ability understanding using the SQ3R method in students at SMK Kahuripan 1 Jakarta. Data collection techniques in this research are interviews, student observation, tests/performance, and and using questionnaires. Characteristic analysis techniques qualitative. Research results regarding improving reading ability understanding using the SQ3R method in students at SMK Kahuripan 1 Jakarta divided into three, namely: 1) increasing students' liking for language lessons Indonesia, 2) increase in reading comprehension ability results, 3) increase student activities in learning Indonesian.